The antidysbiotic and antiphlogistic actions of quertulin at the experimental toxic hepatitis - Levitsky, A. P.; Bocharov, A. V.; Furdychko, A. I.; Stepan, V. T.; Vasyuk, V. L. (Journal of Education, Health and Sport, 2017)
Aim: To develop of antidysbiotic and antiphlogistic actions of quertulin on rat tissues at he toxic hepatitis. Materials and methods: The hepatitis was made with hydrazine sulfate. Antidysbiotic action was estimated by the correlation of urease and lysozyme, antiphlogistic action was estimated by depression of the levels of elastase and malonic dialdehide (MDA). Quertulin (quercetin + inulin + citrate Ca) was introduced per os in dose of 300 mg/kg in duration 14 days. The objects of investigation were liver, kidney, gum, mucosa of check, intestine and colon, serum. Results: The toxic hepatitis were made the raising levels of urease, elastase, MDA and depressing level of lysozyme. Quertulin was depressed of levels of urease, elastase, MDA and was raised of lysozyme level. Conclusion: The toxic hepatitis was developed dysbiosis and inflammation in the rat tissues. Quertulin was made antidysbiotic and antiphlogistic actions, much expressed in colon.